Phase Inversion of Pickering Emulsions Induced by Interfacial Electrostatic Attraction - Sun, Guanqing (Langmuir : the ACS journal of surfaces and colloids, 2023)
Phase inversion of Pickering emulsions from water-in-oil (W/O) to oil-in-water (O/W) is achieved by the formation of an interfacial particle bilayer using negatively charged and positively charged particles dispersed in water and oil, respectively, before emulsification. A mechanism based on electrostatic attraction across the toluene-water interface is proposed and verified by systematic investigation of the parameters that affect the surface charge of negatively charged particles such as pH and salt concentration. Cationic silica-FITC particles (600 nm) can be dispersed in toluene and stabilize W/O emulsions alone; phase inversion of this emulsion can be induced by the addition of anionic silica-RB particles in the aqueous phase at a concentration of 1.0 wt % or above. It is revealed that silica-RB particles of a smaller size (100 nm) can induce emulsion phase inversion at a much lower concentration (0.4 wt %) and an interfacial particle bilayer is clearly revealed by CLSM and SEM images. By tuning the surface charge density of silica-RB particles, the electrostatic attraction mechanism leading to the formation of the interfacial particle bilayer is confirmed and emulsion stability can be tuned as demonstrated by osmotic pressure enhancement results obtained from centrifugation